Snoring in Portuguese primary school children - Ferreira, AM (2000)
OBJECTIVE: To determine the prevalence of snoring and its potential associations with sleep problems, such as daytime symptoms, medical conditions, school performance, and behavioral disturbances in Portuguese children attending primary school. METHODS: A previously validated questionnaire was sent to the parents of 1381 children attending primary schools in a parish of Coimbra, Portugal. To assess behavioral disturbances, the Portuguese version of Rutter's Children's Behavior Questionnaire for completion by teachers was used. RESULTS: Of the 988 questionnaires returned (71.5%), complete information concerning snoring was obtained for 976 children (496 girls and 480 boys; mean age: 8.1 +/- 1.5 years). Loud snoring during sleep was reported as frequent or constantly present (LSn) in 84 children (8.6%), as occasionally present in 299 children (30.6%), and as never present (NSn) by 593 children (60.8%). The LSn and NSn groups did not differ with respect to age, gender, sleep duration, time to fall asleep, frequency of night wakings, bedwetting, daytime tiredness, and school achievement. However, LSn was significantly associated with increased bedtime problems (fears and struggles), increased need for comforting activities to fall asleep, behaviors suggestive of parasomnias (sleep talking, teeth grinding, and night terrors), increased daytime sleepiness and irritability, and behavioral disturbances. Children in the LSn group were also more likely to report recurrent medical problems particularly those involving infections of the respiratory tract. CONCLUSIONS: Snoring is a common symptom in Portuguese children that is associated with behavioral daytime and sleep time disturbances. Children with loud snoring may benefit from early evaluation and intervention.